Instruction in a Strategy for Compare–Contrast Writing - MacArthur, Charles A.; Philippakos, Zoi (Exceptional children, 2010)
Students learned a strategy for planning, writing, and evaluating compare–contrast essays. Instruction followed the principles of self-regulated strategy development, which aims to improve knowledge about writing, strategic writing processes, self-regulation, and motivation. Six adolescent students, 3 with learning disabilities in writing and 3 average writers, were taught in pairs in a multiple baseline design. All students made substantial gains in text structure elements (percentage of non-overlapping data [PND] = 100%) and in overall writing quality (PND = 85%). Gains in mean quality scores for individual students ranged from 1.2 to 3.2 on a 6-point scale. Gains in text structure elements were maintained for the 4 students who could be assessed; gains in quality were maintained for 2 students. Self-efficacy increased for all students.